Coaxial Scale‐Up Printing of Diameter‐Tunable Biohybrid Hydrogel Microtubes with High Strength, Perfusability, and Endothelialization. (3rd September 2020) - Liang, Qingfei; Gao, Fei; Zeng, Zhiwen; Yang, Jirong; Wu, Mingming; Gao, Chongjian; Cheng, Delin; Pan, Haobo; Liu, Wenguang; Ruan, Changshun
Abstract: Although great progress has been made in coaxial extrusion printing toward generating microtubes for mimicking tubular tissues, these microtubes with insufficient mechanical properties and uncontrollable inherent swelling attribute severely hinder their utilization as load‐bearing tubular tissue. Herein, a high‐strength microtube is constructed by coaxial printing with a customized biohybird hydrogel ink consisting of nanoclay, H‐bonding monomer N‐acryloyl glycinamide, and gelatin methacryloyl. The physical interpenetration between nanoclay and polymer chains endows this ink with excellent printability and structural stability, thus facilitating the precise deposition of scalable microtubes with tunable small‐diameters and large‐scale lengths. After photocrosslinking, 3D‐printed biohybrid hydrogel microtube demonstrates marvelous mechanical properties with a tensile strength (≈22 MPa), a stretchability (≈500%), a Young's modulus (≈21 MPa), an anti‐fatigue performance (≈200 cycles), a burst pressure (≈2500 mmHg), and a suture retention strength (≈280 gf) in swelling equilibrium state, which are far superior to the previously printed microtubes and generally satisfy the requirements of tubular tissues. Additionally, this obtained microtube also displays favorable biological features that support adhesion, spreading, and endothelialization of human umbilical vein endothelial cells. This study successfully develops a biohybrid hydrogel ink to fabricate a scalable high‐strength microtube with enormous potential in regeneration of tube‐like tissues. Abstract : A high‐strength hydrogel microtube is fabricated based on a customized biohybird hydrogel ink through a coaxial printing system. These 3D‐printed microtubes demonstrate tunable diameters, excellent mechanical properties, as well as biocompatiblity, thus providing a facile and scalable strategy for mimicking and tailoring tube‐like tissues.